Implications of moderate altitude training for sea-level endurance in elite distance runners - Bailey, D. M.; Davies, B.; Romer, L.; Castell, L.; Newsholme, E.; Gandy, G. (European Journal of Applied Physiology, 1998)
Elite distance runners participated in one of two studies designed to investigate the effects of moderate altitude training (inspiratory partial pressure of oxygen ≈115-125 mmHg) on submaximal, maximal and supramaximal exercise performance following return to sea-level.